Clinical significance of tumor cavitation in surgically resected early-stage primary lung cancer. (October 2017) - Tomizawa, Kenji; Shimizu, Shigeki; Ohara, Shuta; Fujino, Toshio; Nishino, Masaya; Sesumi, Yuichi; Kobayashi, Yoshihisa; Sato, Katsuaki; Chiba, Masato; Shimoji, Masaki; Suda, Kenichi; Takemoto, Toshiki; et al.
Highlights: Fifty-nine of 602 patients had tumor cavitation (10%). Lung cancers with tumor cavitation showed high metabolic activity. Tumor cavitation is a negative prognostic factor for primary lung cancer. Patients with tumor cavitation should be regarded as a separate cohort. Abstract: Objectives: The prognostic impact of tumor cavitation is unclear in patients with early-stage primary lung cancer. The aim of the present study was to examine the clinicopathological features and prognoses of patients with pathological stage I–IIA (p-stage I–IIA) primary lung cancers harboring tumor cavitation. This study was conducted according to the eighth edition of the TNM classification for lung cancer. Materials and methods: We examined 602 patients with p-stage I–IIA primary lung cancer out of 890 patients who underwent pulmonary resection from January 2007 through March 2014 and searched for the presence of tumor cavitation, which is defined as the presence of air space within the primary tumor. Results: A total of 59 out of the 602 patients had tumor cavitation (10%). Compared with patients without tumor cavitation, those with tumor cavitation had a significantly higher frequency of the following characteristics: high serum carcinoembryonic antigen (CEA) level (≥5 ng/ml, p = 0.027), interstitial pneumonia (p = 0.0001), high SUVmax value on FDG-PET scan (≥4.2, p = 0.023), tumors located in the lower lobe (p = 0.024), large tumor size (>3 cm, p = 0.002), vascular invasion (66% vs 17%, p < 0.0001) and non-adenocarcinoma histology (p = 0.025). The overall survival period of patients with tumor cavitation was significantly shorter than that of patients without tumor cavitation (log-rank test: p < 0.0001, 5-year OS rate: 56% vs 81%). Tumor cavitation was found to be an independent and significant factor associated with poor prognosis in the multivariate analysis (hazard ratio: 1.76, 95% confidence interval: 1.02–3.10, p = 0.042). Conclusions: Tumor cavitation is an independent factor for poor prognosis in patients with resected p-stage I–IIA primary lung cancer. Based on our analyses, patients with tumor cavitation should be regarded as a separate cohort that requires more intensive follow-up.